Experimental and numerical comparison of equal channel angular extrusion (ECAE) with planar twist channel angular extrusion (PTCAE). (November 2015) - Shamsborhan, Mahmoud; Shokuhfar, Ali; Nejadseyfi, Omid; Kakemam, Jamal; Moradi, Mahmoud
Planar twist channel angular extrusion (PTCAE) is a new severe plastic deformation (SPD) method to impose large strain and to increase the efficiency of SPD methods. This novel process was conducted on commercially pure aluminum and was investigated by finite element analysis and experimental tests. The results revealed that performing PTCAE made it possible to impose large strain values per pass while maintaining a homogenous hardness distribution on the cross-section of sample. The objective of this paper is comparison of hardness after one pass of PTCAE and equal channel angular pressing (ECAP) processed samples. The results revealed that an increase in the hardness from 29 Hv to ∼49 Hv and ∼41 Hv could be achieved after one pass of PTCAE and ECAP, respectively. PTCAE process has two important advantages of inducing higher plastic strain and excellent strain and hardness homogeneity. Therefore, PTCAE is a promising SPD technique for specific applications to produce ultrafine-grained or nanostructured materials.